Potential improvement in combustion behavior of a downsized rotary engine by intake oxygen enrichment. (1st February 2020) - Shi, Cheng; Ji, Changwei; Wang, Shuofeng; Yang, Jinxin; Ma, Zedong; Meng, Hao
Highlights: Implementation of oxygen enriched air on rotary engine combustion was performed. Thorough 3D CFD models of rotary engines was built and verified by experiment data. Increasing oxygen content stimulated the growth of initial flame and burned volume. Oxygen enrichment markedly reduced the formations of CO, HC, and soot emissions. The optimum combustion behavior can be achieved by αO2  = 30% and λ = 1.1 operation. Abstract: The attractiveness of oxygen-enriched combustion advantages are making a comeback in the implementation of the rotary engine concept. In this connection, a numerical investigation on influences of intake oxygen enrichment combined with excess air ratio on combustion behavior of the rotary engine needs to be clarified. A three-dimensional computational fluid dynamics simulations coupling with chemical kinetic mechanisms was performed in this study, and the numerical results had been validated with existing experimental data. The species evolution, combustion characteristics, and pollutant formation were monitored to assess the oxygen-enriched combustion of the rotary engine. Results showed that there was a significant influence of intake oxygen enrichment for improving flame development and burned volume due to the reasonable species concentration and intense turbulence intensity. Increasing oxygen enrichment led to the enhanced peak pressure and advanced corresponding position, resulted in a rapid combustion period for improving heat-release efficiency and combustion efficiency, meanwhile made a higher indicated mean effective pressure at the price of a smaller increment of nitrogen oxide formation. The substantial reductions of carbon monoxide, unburned hydrocarbon, and soot were recorded, which is attributed to the higher-oxygen mixture with suitable lean operations. Considering combustion characteristics and emissions performance, the operation of intake oxygen volume of 30% accompanying the excess air ratio of 1.1 is the best choice for the engine used in the current study.